Group transdiagnostic cognitive-behavior therapy for anxiety disorders: a pragmatic randomized clinical trial. Issue 13 (2nd October 2022) - Roberge, Pasquale; Provencher, Martin D.; Gaboury, Isabelle; Gosselin, Patrick; Vasiliadis, Helen-Maria; Benoît, Annie; Carrier, Nathalie; Antony, Martin M.; Chaillet, Nils; Houle, Janie; Hudon, Catherine; Norton, Peter J.
Abstract: Background: Transdiagnostic group cognitive-behavioral therapy (tCBT) is a delivery model that could help overcome barriers to large-scale implementation of evidence-based psychotherapy for anxiety disorders. The aim of this study was to assess the effectiveness of combining group tCBT with treatment-as-usual (TAU), compared to TAU, for the treatment of anxiety disorders in community-based mental health care. Methods: In a multicenter single-blind, two-arm pragmatic superiority randomized trial, we recruited participants aged 18–65 who met DSM-5 criteria for principal diagnoses of generalized anxiety disorder, social anxiety disorder, panic disorder, or agoraphobia. Group tCBT consisted of 12 weekly 2 h sessions. There were no restrictions for TAU. The primary outcome measures were the Beck Anxiety Inventory (BAI) and clinician severity rating from the Anxiety and Related Disorders Interview Schedule for DSM-5 (ADIS-5) for the principal anxiety disorder at post-treatment, with intention-to-treat analysis. Results: A total of 231 participants were randomized to either tCBT + TAU (117) or TAU (114), with outcome data available for, respectively, 95 and 106. Results of the mixed-effects regression models showed superior improvement at post-treatment for participants in tCBT + TAU, compared to TAU, for BAI [ p < 0.001; unadjusted post-treatment mean (s.d. ): 13.20 (9.13) v. 20.85 (10.96), Cohen's d = 0.76] and ADIS-5 [ p < 0.001; 3.27 (2.19) v. 4.93 (2.00), Cohen's d = 0.79]. Conclusions: Our findings suggest that the addition of group tCBT into usual care can reduce symptom severity in patients with anxiety disorders, and support tCBT dissemination in routine community-based care.